The Effect of Co-Administration of Telang Leaves Ethanolic Extract Towards Fluoxetin’s Sedative Effect on Male Balb/C Mice Based on Sleeping Duration Parameter - Anif Nur Artanti; Maria Ulfah (Indonesian Journal of Cancer Chemoprevention, 2015)
One of Telang plant’s advantages is its activity as sedative agent. Previous studies indicate that Telang plant has anticonvulsant activity on mice at certain dose. This study was conducted to find out the sedative effect of Telang plant, particularly its leaf, when being co-administered with fluoxetin. Phytochemical analysis was carried out qualitatively on Telang ethanolic extract leaves (TEE) to find out the content of chemical compound first.This study was an experimental research with post-test only control group design, employing male balb/c mice. The effect of Telang ethanolic extract co-administration with fluoxetin was observed. The parameter being used in the study was the duration of sleep. Analysis was done by comparing mice sleeping duration prior to administration of fluoxetin alone and in combination with Telang ethanolic extract. The data was then analyzed using SPSS 17.0 for Windows.The results showed that TEE contained tannin, saponin, and flavonoid compounds, and co-administration of TEE and fluoxetin at various doses could provide sedative effect on mice. The co-administration of 400 mg/kgBW extract and 15 mg/kgBW fluoxetin could provide the mean sleeping duration 43 minutes longer than positive control.Keywords:  telang leaves ethanol extract, fluoxetin, sleeping duration